Profundidad de alcance en un contexto de comercialización de las microfinanzas en el Perú - Valenzuela Ramírez, Irina E. (2011)
This paper seeks to answer the question of what factors are conducive to depth of outreach, that is, attending to customers on lower incomes, on the part of commercial microfinance institutions (MFIs) in Peru, in order to propose measures aimed at increasing the financial inclusion of the microenterprise sector. Using a panel database containing information on the MFIs regulated by Peru’s banking, insurance, and pension fund management comptroller (Superintendencia de Banca, Seguros y AFP) and regressions with panel-corrected standard errors, the study finds that depth of outreach would benefit from lower administrative costs per borrower, the specialization of MFI loans to micro-entrepreneurs, and higher interest rates, the first two variables being those proposed by the present investigation. Meanwhile, the trade-off between MFI depth and profitability , discussed widely in the literature on the subject, would also be present in commercial MFIs. Additionally, those bodies who promote micro-enterprise development would present the greatest potential for further deepening.